Validation of method for cannabis identification using gas chromatography technique - Dragoljić, Mirjana; Matić, Vesna; Simurdić, Ljiljana (Journal of Engineering & Processing Management, 2017)
The methods of analysis in forensic must be reliable in order for the results of the analysis to be accepted as evidence in court proceedings. The reliability of methods is checked through the validation process, which should be performed before introducing a method into the routine practice of the laboratory. This paper describes the procedure for identification of Cannabis sativa L. plant and its preparations (resin - "hašiš", oil) using a gas chromatography technique with a flame ionization detector, as well as the validation procedure of the method by which identify three basic cannabinoids: psychoactive tetrahydrocannabinol, cannabidiol and cannabinol. The method validation process includes the necessary equipment, the description of the required performance of the analytical method, the conducting of the tests, the way and the criteria for evaluation validation results.